2004
DOI: 10.1007/s00122-003-1471-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection and verification of quantitative trait loci for resistance to Dothistroma needle blight in Pinus radiata

Abstract: Six related radiata pine ( Pinus radiata) full-sib families were used to detect and independently verify quantitative trait loci (QTLs) for resistance to Dothistroma needle blight, caused by Dothistroma septospora. The detection families had from 26 to 30 individuals each, and had either a common maternal (31053) or paternal (31032) parent; one family (cross 4) consisted of progeny from both parents, 31053 x 31032. Approximately 200 additional progeny from cross 4 were clonally replicated and planted at two si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Studies in the same species have detected up to 34 % of segregation distortion (Kuang et al 1999), however the smaller number of offspring compared to earlier studies (Wilcox et al 2001, Devey et al 2004 could be responsible for the low representativeness of the expected allelic proportions.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Studies in the same species have detected up to 34 % of segregation distortion (Kuang et al 1999), however the smaller number of offspring compared to earlier studies (Wilcox et al 2001, Devey et al 2004 could be responsible for the low representativeness of the expected allelic proportions.…”
Section: Resultsmentioning
confidence: 62%
“…Polymorphic information, mode of inheritance, genomic size and complexity are factors that influence the development of a particular technique and the selection of informative molecular markers (Plomion et al 2007). Among the molecular techniques implemented for P. radiata are restriction fragment length polymorphism (RFLP; Devey et al 2004), random amplified polymorphic DNA (RAPD; Kuang et al 1999, Wilcox et al 2001, amplified fragment length polymorphism (AFLP; Wilcox et al 2001), simple sequence repeat (SSR; Fisher et al 1998, Devey et al 2002, Chagné et al 2004) and single-nucleotide polymorphism (SNP; Dillon et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, Franich et al (1986) reported an opposite effect and therefore concluded that dothistromin-induced lesion length was not a good measure of field resistance in Pinus radiata. Devey et al (2004) were able to identify quantitative trait loci for DNB resistance in P. radiata in Australia, which can be used as markers for DNB resistance and should contribute to future resistance breeding.…”
Section: Breeding For Resistancementioning
confidence: 99%
“…Currently, the disease is managed in Southern Hemisphere plantations by the aerial application of copper fungicides (Bradshaw 2004), which can be costly and have detrimental effects on the environment (Devey et al 2004). Reduction in disease is also obtained through breeding programs for Dothistroma septosporum resistant pine strains.…”
Section: Forest Managementmentioning
confidence: 99%
“…Quantitative traits can be selected for through long term breeding programs, or by selecting individuals that have a genetic marker associated with quantitative resistance (Devey et al 2004). Breeding programs have been underway in New Zealand for some time now and have been effective in reducing overall losses (Bradshaw 2004).…”
Section: Forest Managementmentioning
confidence: 99%